Predictors of complementary feeding practices in Afghanistan: Analysis of the 2015 Demographic and Health Survey. (29th November 2018) - Na, Muzi; Aguayo, Víctor M.; Arimond, Mary; Mustaphi, Piyali; Stewart, Christine P.
Abstract: Despite improvements over the past 20 years, high burdens of child mortality and undernutrition still coexist in Afghanistan. Global evidence indicates that complementary feeding (CF) practices predict child survival and nutritional status. Our study aims to describe CF practices in Afghanistan and to discern underlying predictors of CF by analysing data from Afghanistan's 2015 Demographic and Healthy Survey. Multilevel models were constructed comprising potential predictors at individual, household, and community levels and four CF indicators: timely introduction of solid, semi‐solid, or soft foods (INTRO), minimum meal frequency (MMF), minimum dietary diversity (MDD), and minimum acceptable diet (MAD) among breastfed children. INTRO prevalence among children aged 6–8 months was 56%, whereas the prevalence of MMF, MDD, and MAD among children aged 6–23 months was 55%, 23%, and 18%, respectively. Of the seven food groups considered, four were consumed by 20% or fewer children: eggs (20%), legumes and nuts (18%), fruits and vegetables (15%), and flesh foods (14%). Increasing child age and more antenatal care visits were significantly and positively associated with greater odds of meeting all CF indicators. Lower household wealth and lower community‐level access to health care services were associated with lower odds of MDD and MAD. Disparities in achieving recommended CF practices were observed by region. CF practices in Afghanistan are poor and significant socioeconomic inequities in CF are observed across the country. Our study calls for urgent policy and programme attention to improve complementary feeding practices as an intrinsic part of the national development agenda.